Decanucleotide insertion polymorphism of F7 significantly influences the risk of thrombosis in patients with essential thrombocythemia. (23rd April 2014) - Buxhofer‐Ausch, Veronika; Olcaydu, Damla; Gisslinger, Bettina; Schalling, Martin; Frantal, Sophie; Thiele, Jürgen; Müllauer, Leonhard; Kvasnicka, Hans‐Michael; Watzke, Herbert; Kralovics, Robert; Gisslinger, Heinz
Abstract Objective There is strong evidence that certain thrombophilic single nucleotide polymorphisms (SNPs) account for an increased risk of thrombosis. The additive impact of inherited thrombotic risk factors to a certain disease‐ immanent thrombotic risk is vastly unknown. Therefore, we aimed to investigate the influence of three novel, preselected SNPs on the risk of thrombosis in patients diagnosed with myeloproliferative neoplasm (MPN). Method In 167 patients with a diagnosis of essential thrombocythemia (ET) or prefibrotic primary myelofibrosis (PMF) thrombophilic SNPs in the genes of factor VII (F7), nitric oxide synthase 3 (NOS3) and FcɣRIIa (FCGR2A) were determined. Subsequently, the polymorphic variants were correlated with the incidence of major thrombosis after diagnosis. Results Decanucleotide insertion polymorphism of F7 emerged as an independent, significant risk factor for total thrombosis and arterial thrombosis in particular in the whole group of patients (P = 0.0007) as well as in the separate analysis of patients with ET (P = 0.0002). Conclusion Our results illustrate that the risk of thrombosis in MPN is significantly multiplied by inherited thrombophilic SNPs. This result points to the importance of a combined consideration of the inherited and the acquired hypercoagulable state in patients with MPN. Larger studies are needed to confirm and extend these important findings.